2021
DOI: 10.3389/fpsyg.2021.685815
|View full text |Cite
|
Sign up to set email alerts
|

Validating Visual Stimuli of Nature Images and Identifying the Representative Characteristics

Abstract: This study fills a void in the literature by both validating images of nature for use in future research experiments and examining which characteristics of these visual stimuli are found to be most representative of nature. We utilized a convenience sample of university students to assess 129 different nature images on which best represented nature. Participants (n = 40) viewed one image per question (n = 129) and were asked to rate images using a 5-point Likert scale, with the anchors “best represents nature”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…While both of these explanations can be true, it is also the case that certain characteristics of forest settings such as big trees and waterfalls are consistently associated with people's landscape preferences and are reported to produce "peak" aesthetic and other highly valued experiences for people [226,237]. In our review we identified a small number of studies that looked at preference and suitability as outcome measures, which seemed better able to discriminate between forest setting characteristics than standardized psychological and physiological indicators [57,60,156]. However, there is also an extensive research literature on landscape perception and preference [30,238], that except for selected studies [75,239] has not been linked to forest therapy research to date.…”
Section: Forest Componentmentioning
confidence: 97%
See 1 more Smart Citation
“…While both of these explanations can be true, it is also the case that certain characteristics of forest settings such as big trees and waterfalls are consistently associated with people's landscape preferences and are reported to produce "peak" aesthetic and other highly valued experiences for people [226,237]. In our review we identified a small number of studies that looked at preference and suitability as outcome measures, which seemed better able to discriminate between forest setting characteristics than standardized psychological and physiological indicators [57,60,156]. However, there is also an extensive research literature on landscape perception and preference [30,238], that except for selected studies [75,239] has not been linked to forest therapy research to date.…”
Section: Forest Componentmentioning
confidence: 97%
“…Survey research (n = 15, 5.6%) included both large-scale general population surveys [54] and targeted onsite intercept surveys of forest visitors engaged or interested in forest therapy experiences [55,56]. Research types used in less than 10 articles included expert assessments such as suitability analyses [57,58] and site inventories [59], image analysis of virtual landscape representations [60] and social media selfie posts [61], and epidemiological studies [62].…”
Section: Study Sample Characteristicsmentioning
confidence: 99%
“…Nurses can introduce nature-based virtual reality, YouTube videos, or still photographs for patients to visualize. Pictures with canopies of vegetation, bodies of water, and mountains were identified in one study as best representing nature (Menser et al, 2021). If your hospital does not have the technology for this, strategize with the governance team or chaplains as to how this may be acquired.…”
mentioning
confidence: 99%